L'armement charbonnier Marcesche (1898-1939) - Pascal Boisson (Codrul Cosminului, 2012)
In France, Lorient, city located in Brittany, is representative of the medium-sized ports. But how to explain the creation of an industrial and coal shipyard group in the last years of the 19th century in the port of Lorient? It is definitely not the port's conjecture which was then buoyant. Ranked seventeenth by its traffic, its rating is finally excellent, for Lorient, which was still suffering from its past and the absence of hinterland, benefited from a self-centered development around coal, the only path of sustainable growth, which the manufacturer Emile Marcesche had perfectly understood.Emile Marcesche is a new man. From Anjou, he is fatherless and comes from a wine-growers family and is a pure product of the non-religious school of which he manages to be a brilliant superior primary school teacher in Angers. In short, an intellectual. His success is linked to his settling down in the maze of the Lorient notables. But what are the conditions of this settling down? Marcesche, through his marriage, is introduced to a Lorient elite, very marked politically speaking, royalist and catholic. He is thrown into this background, a very conservative and reactionary politic melting-pot. But one of the keys to understand his path, is that, thanks to his in-laws' network, he has an easy passage into the world of preserve manufactures, at the head of one of the biggest preserve industrial groups in South Brittany, with different sites in numerous Breton ports, from Audierne to Quiberon, but also in Portugal, Morocco and Algeria. Those manufacturers will supply Marcesche wit the necessary capitals, notably to constitute an important steamer ships fitting out.Marcesche appears like a very pragmatic man, but with intuition. He maximizes his fitting out function by investing in the setting up of a subsidiary in Cardiff, which he entrusts with Marcel Ragody, to give it a scale that exceeds the simple service to the firm Marcesche. With its offices in the other Welsh ports, it becomes one of the first houses concerning coal export towards the French and even foreign ports and the essential go-between of numerous mine-posts suppliers with Welsh firms.